2011
DOI: 10.1111/j.1460-9592.2011.03654.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C: influence of perfusion and myocardial injury on early (<24 h) renal function after pediatric cardiac surgery

Abstract: Cystatin C is a sensitive marker of early renal dysfunction following pediatric heart surgery. Variations in bypass parameters, myocardial injury, and ultimately critical oxygen delivery are significantly associated with the degree of renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies in the recent literature have evaluated serum Cys C as an early marker of AKI, as well as its severity, in children sustaining AKI secondary to CPB . They have shown that it is a good marker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in the recent literature have evaluated serum Cys C as an early marker of AKI, as well as its severity, in children sustaining AKI secondary to CPB . They have shown that it is a good marker.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the recent literature have evaluated serum Cys C as an early marker of AKI, as well as its severity, in children sustaining AKI secondary to CPB. [7][8][9][10][11] They have shown that it is a good marker. But all of these studies are limited by the fact that AKI was defined using either serum Cr or Cr-based estimations of GFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible disadvantages of CysC are its dependency on factors other than decline of renal function alone, such as age, gender, weight and height, smoking and high serum C‐reactive protein concentrations . In the clinic, CysC has been shown to be a sensitive marker of early renal dysfunction following ischaemic injury .…”
Section: Summary On Selected Markersmentioning
confidence: 99%